2021
DOI: 10.3390/nu13051675
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Post-Surgical Nutrition for Preservation of Muscle Mass, Strength, and Functionality Following Orthopedic Surgery

Abstract: Nutritional status is a strong predictor of postoperative outcomes and is recognized as an important component of surgical recovery programs. Adequate nutritional consumption is essential for addressing the surgical stress response and mitigating the loss of muscle mass, strength, and functionality. Especially in older patients, inadequate protein can lead to significant muscle atrophy, leading to a loss of independence and increased mortality risk. Current nutritional recommendations for surgery primarily foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 67 publications
0
74
0
2
Order By: Relevance
“…Recently, a randomized controlled clinical trial conducted by Juhasz et al (2018) [ 57 ] concluded that CrM supplementation (20 g for 5 days followed by 5 g for the rest of the study) combined with therapeutic strategy effectively supports the rehabilitation of tendon overuse injury of adolescent fin swimmers. A recent systematic review that evaluated pre- and post-surgical nutrition for preservation of muscle mass, strength, and functionality also concluded that CrM supplementation merits consideration in the general population [ 99 ]. In agreement with the collective body of evidence reviewed in this systematic integrative review, we adhere to this recommendation considering the very good safety profile of CrM at doses of 0.1 g/kg/day.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a randomized controlled clinical trial conducted by Juhasz et al (2018) [ 57 ] concluded that CrM supplementation (20 g for 5 days followed by 5 g for the rest of the study) combined with therapeutic strategy effectively supports the rehabilitation of tendon overuse injury of adolescent fin swimmers. A recent systematic review that evaluated pre- and post-surgical nutrition for preservation of muscle mass, strength, and functionality also concluded that CrM supplementation merits consideration in the general population [ 99 ]. In agreement with the collective body of evidence reviewed in this systematic integrative review, we adhere to this recommendation considering the very good safety profile of CrM at doses of 0.1 g/kg/day.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 , 13 ] Studies have shown that the probability of elbow stiffness after trauma is at least 5%, and if the range of motion of the elbow is less than 30° to 120°, it will seriously affect orthobiosis. [ 14 ] If functional exercise had been performed after complete healing of the fracturs, the limb is prone to suffer from apraxia osteoporosis, heterotopic ossification, [ 15 ] muscle atrophy around the elbow joint, [ 16 ] and adhesion of the elbow joint derived from hematoma. Therefore, the range of motion and function of the elbow will be remarkably restricted.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the occurrence of a more catabolic state during the surgery period, there occurs the destruction of many important inorganic as well as organic elements (for example nitrogen and protein loss) in the body, altering the speed of wound healing [ 52 ]. One of them is the decrement of serum albumin, commonly observed in most patients [ 53 ] which is the result of intense surgical stress predicting increased postoperative complications [ 54 ].…”
Section: Discussionmentioning
confidence: 99%